Determinant of Employee Engagement Based on Transformational Leadership, Compensation, and Work Environment at Lasmono Group in Surabaya - Zalman Alfarizt; Jojok Dwiridotjahjono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of transformational leadership, compensation, and work environment on employee engagement at Lasmono Group in Surabaya. The research was prompted by a strategic paradox within the company: despite low employee turnover rates suggesting high satisfaction, the actual level of employee engagement remained unmeasured, posing a risk of